PENGARUH PENERAPAN PEMBELAJARAN INQUIRI DAN METODE DEMONSTRASI TERHADAP HASIL BELAJAR PADA MATA PELAJARAN FIQHI PESERTA DIDIK KELAS XI DI MADRASAH ALIYAH GUPPI SAMATA KABUPATEN GOWA - ., Nurdalia; ., Susdiyanto; Saat, Sulaiman (Inspiratif Pendidikan, 2018)
This problem aims to find out the application of inquiry learning on fiqhi subjects, find out the application of demonstration methods on fiqhi subjects, find out the learning outcomes on fiqhi subjects of class XI students after pre-test and post-test at Aliyah Guppi Samata Gowa District, to know the influence the application of inquiry learning on subjects, knowing the effect of applying the demonstration method on fiqhi subjects, knowing the effect of the application of inquiry learning and demonstration methods on fiqhi subjects of class XI students at the Aliyah Guppi Samata Madrasah in Gowa Regency simultaneously. This research is a quasi-experimental design by dividing the two groups, namely the experimental class and the control class which are chosen non-equivalently without randomization, then given a pre-test to find out what is the initial difference between the control class and the experimental class, after which through post-test on the control class and experiment. This study uses quantitative analysis, in Aliyah Guppi Samata Madrasah Gowa Regency, amounting to 40 students, the method of data collection is taken in three ways, namely observation, tests and documentation. Data processing techniques were first tested for validity, reliability of the test items collected in the field, then analyzed descriptively statistically, inferential tests (consisting of normality test, linearity test), hypothesis testing (including simple regression analysis and multiple regression analysis. First , the results of the study state that the application of inquiry learning can improve the learning outcomes of fiqhi subjects, the second application of demonstration methods can improve learning outcomes in fiqhi subjects, thirdly obtain inquiry learning learning outcomes more significantly than the control class on variable X. Pretest IV in the value control class the average is 54.95, the application of inquiry learning has an average score of 60.35, post-test IV in the control class has an average score of 62.7, the application of inquiry learning has an average value of 79.00, then the application of the demonstration method is more significant compared to the control class in Variable X 2. Pretest IV in the control class the average value was 52.55, the demonstration method averaged 65.30. Post-test IV test in the control class averaged 51.65, and the demonstration method averaged 74.30, fourth obtained the influence of the determination coefficient of 71.8%, fifth, there was an influence between the application of demonstration methods to learning outcomes fiqhi subjects in Aliyah Madrasah Guppi Samata Gowa Regency, the magnitude of the influence of the determination coefficient of 78.1% and sixth there is a joint effect between the application of inquiry learning and demonstration methods on learning outcomes fiqhi subjects in Madrasah Aliyah Guppi Samata Gowa Regency determination coefficient of 78.8%.